FUTSAL SHOOTING TRAINING MODEL FOR EXTRACURRICULAR HIGH SCHOOL STUDENTS - Ader Damar Indrawan; Susilo; Aan Wasan; Rizka Antoni (UNIVERSITAS NEGERI JAKARTA POSTGRADUATE OF PHYSICAL EDUCATION DEPARTMENTS, 2021)
Abstract The purpose of this study was to provide an overview of a variety of models of training in futsal shooting techniques that are effective for high school extracurricular students. To find out that the design product of a new training model or perfecting previous research is complete with product specifications as well as testing the effectiveness of the training model created, so that it can improve accuracy and quality and can be used as a guide for playing futsal games in the form of shooting. Based on the data obtained from the expert / expert test results and implementation to the futsal extracurricular trainer, it can be concluded that this training model is feasible to be applied in practicing futsal shooting skills. The subjects in this study were students who were members of the extracurricular activities at KORPRI higj school and Al-Muslim high school. The research method used is (Research and Development) from ADDIE which consists of 5 steps, namely analysis, design, development, implementation, evaluation. There are 23 models of futsal shooting practice.